Valoración del Paisaje natural del Bosque Siempreverde Piemontano (BsPn01) de la Cordillera Occidental de los Andes en la Provincia de Cotopaxi en el periodo 2020 - 2021 - Itas López, Milton Javier (2021)
This research project was developed in order to assess the quality of the natural landscape of the Evergreen Piemontano Forest (BsPn01) of the Western Cordillera of the Andes, located in the Province of Cotopaxi between the Cantons La Maná, Pangua and Pujilí. For this, the analysis of the natural landscape conditions of the forest was established and a method focused on determining the visual fragility of the landscape was proposed, the methodology that was applied was based on the guidelines established by the Bureau of Land Management (BLM) method. ) who determined to establish quali-quantitative values established in numerical weighting scales focused on the determination of the components (texture, color, relief, erodibility, slope, vegetation, scenic context) that form the landscape units based on subjective evaluations presented by the researcher through the analysis of photographs of the study area; For this, field visits and surveys were established based on non-probabilistic random sampling in order to know directly the different activities that take place in the place. The results show that photograph 1 presents a high visual quality and a medium fragility, therefore it requires management and conservation activities, while in photograph 2 it can be evidenced that it presents a high visual quality and low fragility, for which does not require conservation activities; On the other hand, when analyzing photograph 3, among its results, it presents a medium visual quality and high fragility, which is why it requires a restoration in its landscape units, based